Unmanipulated haploidentical hematopoietic stem cell transplantation for pediatric de novo acute megakaryoblastic leukemia without Down syndrome in China: A single-center study - Huang, Junbin; Hu, Guanhua; Suo, Pan; Bai, Lu; Cheng, Yifei; Wang, Yu; Zhang, XiaoHui; Liu, KaiYan; Sun, YuQian; Xu, LanPing; Kong, Jun; Yan, ChenHua; et al. (Frontiers in Oncology, 2023)
Background: AMKL without DS is a rare but aggressive hematological malignant disease in children, and it is associated with inferior outcomes. Several researchers have regarded pediatric AMKL without DS as high-risk or at least intermediate-risk AML and proposed that upfront allogenic hematopoietic stem cell transplantation (HSCT) in first complete remission might improve long-term survival. Patients and method: We conducted a retrospective study with twenty-five pediatric AMKL patients without DS who underwent haploidentical HSCT in the Peking University Institute of Hematology, Peking University People’s Hospital from July 2016 to July 2021. The diagnostic criteria of AMKL without DS were adapted from the FAB and WHO: ≥ 20% blasts in the bone marrow, and those blasts expressed at least one or more of the platelet glycoproteins: CD41, CD61, or CD42. AMKL with DS and therapy related AML was excluded. Children without a suitable closely HLA-matched related or unrelated donor were eligible to receive haploidentical HSCT. Definition was adapted from international cooperation group. All statistical tests were conducted with SPSS v.24 and R v.3.6.3. Results: The 2-year OS was 54.5 ± 10.3%, and the EFS was 50.9 ± 10.2% in pediatric AMKL without DS undergoing haplo-HSCT. Statistically signiﬁcantly better EFS was observed in patients with trisomy 19 than in patients without trisomy 19 (80 ± 12.6% and 33.3 ± 12.2%, respectively, P = 0.045), and OS was better in patients with trisomy 19 but with no statistical signiﬁcance (P = 0.114). MRD negative pre-HSCT patients showed a better OS and EFS than those who were positive (P < 0.001 and P = 0.003, respectively). Eleven patients relapsed post HSCT. The median time to relapse post HSCT was 2.1 months (range: 1.0–14.4 months). The 2-year cumulative incidence of relapse (CIR) was 46.1 ± 11.6%. Conclusion: AMKL without DS is a rare but aggressive hematological malignant disease in children, and it is associated with inferior outcomes. Trisomy 19 and MRD negative pre-HSCT might contribute to a better EFS and OS. Our TRM was low, haplo-HSCT might be an option for high-risk AMKL without DS.